2018
DOI: 10.1007/s00787-018-1163-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for mental health at a youth mass gathering

Abstract: Mass gatherings may have a net benefit for attendee mental health, especially for those attendees who are subjectively committed to the event. However, a vulnerable subgroup of attendees requires targeted mental health support.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 46 publications
(56 reference statements)
1
20
0
Order By: Relevance
“…Finally, it is important to emphasize that the research does not intend to portray social identity processes as uniquely exacerbating health risks in mass gatherings. The health benefits associated with collective participation (Cruwys et al, 2019;Khan et al, 2015) should not be neglected. Rather, the present research should be seen as contributing to efforts to understand the nature and scope of social identity processes in aggravating and mitigating health risks in mass gatherings (e.g., WHO, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, it is important to emphasize that the research does not intend to portray social identity processes as uniquely exacerbating health risks in mass gatherings. The health benefits associated with collective participation (Cruwys et al, 2019;Khan et al, 2015) should not be neglected. Rather, the present research should be seen as contributing to efforts to understand the nature and scope of social identity processes in aggravating and mitigating health risks in mass gatherings (e.g., WHO, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, pilgrims at a Hindu festival in Indiathe Magh Melareported improved subjective health over time to the extent that they experienced a sense of shared social identity and perceived their relations with other pilgrims to be intimate and supportive (Khan et al, 2015). Similarly, attendees of an Australian festival for school leavers reported mental health benefits to the degree that they identified with other attendees; in contrast, those who experienced psychological distress were more likely to report social isolation and negative attitudes towards other groups in the mass gathering (i.e., other attendees, the police, and volunteers; Cruwys et al, 2019).…”
mentioning
confidence: 99%
“…In turn, there is evidence from an overcrowded music festival that under a shared identity, participants report anticipating support from others and that this contributed to feelings of safety and resilience (Drury, Novelli, & Stott, 2015). So too in a study of youth celebrations marking the end of schooling in Australia, Cruwys et al, (2019) found social identification with the crowd-predicted well-being. Moreover, the relationship between identification and (improved) mental health was stronger among a sample tested later in the event than a sample tested earlier in the event.…”
Section: Mass Gatherings and The "Social Cure"mentioning
confidence: 99%
“…Although many Israelis are motivated to serve in IDF and face the challenges related to the military service ( 10 ), difficulties in adjusting to the new environmental are frequent ( 11 ). While the negative impact of stress on QoL has been well-documented in multiple adolescent populations, such as in those living in high threat environments ( 12 , 13 ), in at-risk youth ( 14 ), in university students ( 15 ) and in college students ( 16 ), little is known about contributors to the QoL of newly recruited soldiers during their BCT in the army worldwide, as most studies examining QoL were conducted in veterans or in combat soldiers after their basic training phase ( 17 , 18 ).…”
Section: Introductionmentioning
confidence: 99%